Reliability of orbital volume measurements based on computed tomography segmentation: Validation of different algorithms in orbital trauma patients. Issue 6 (June 2020) - Chepurnyi, Yurii; Chernohorskyi, Denys; Prykhodko, Danylo; Poutala, Arto; Kopchak, Andriy
Abstract: Purpose: To compare the most common methods of segmentation for evaluation of the bony orbit in orbital trauma patients. Materials and methods: Computed tomography scans (before and after treatment) from 15 patients with unilateral blowout fractures and who underwent orbital reconstructions were randomly selected for this study. Orbital volume measurements, volume difference measurements, prolapsed soft tissue volumes, and bony defect areas were made using manual, semi-automated, and automated segmentation methods. Results: Volume difference values between intact and damaged orbits after surgery using the manual mode were 0.5 ± 0.3 cm 3, 0.5 ± 0.4 cm 3 applying semi-automated method, and 0.76 ± 0.5 cm 3, determined by automated segmentation (р = 0.216); the mean volumes (MVs) for prolapsed tissues were 3.0 ± 1.9 cm 3, 3.0 ± 2.3 cm 3, and 2.8 ± 3.9 cm 3 (p = 0.152); and orbital wall defect areas were 4.7 ± 2.8 cm 2, 4.75 ± 3.1 cm 2, and 4.9 ± 3.3 cm 2 (p = 0.674), respectively. Conclusions: The analyzed segmentation methods had the same accuracy in evaluation of volume differences between two orbits of the same patient, defect areas, and prolapsed soft tissue volumes but not in absolute values of the orbital volume due to the existing diversity in determination of anterior closing. The automated method is recommended for common clinical cases, as it is less time-consuming with high precision and reproducibility.